Webinar on Writing Scientific Articles for Teachers: Strengthening Professionalism Through Publication Literacy - Merri Sri Hartati; Rizki Pratama; Winda Ramadianti; Hardiansyah Hardiansyah; Haniyatul Latifah (Galuh International Journal of Community Service and Development, 2025)
This community service activity aims to improve teachers' capacity in writing scientific articles as part of ongoing professional development. A total of 30 teachers from the Avicena Bengkulu Learning Community participated in a webinar titled "Writing Scientific Articles for Teachers," held online on September 25, 2024, via Google Meet. The activity consisted of delivering materials and facilitating interactive discussions on the structure of scientific articles, adjustments to journal templates, and publication strategies. The activity results showed high enthusiasm among participants, reflected in their active questioning and readiness to prepare the initial draft of the article. This activity increased participants' understanding of the importance of scientific publications and encouraged them to begin writing based on the learning practices they had undertaken. This webinar is a genuine contribution from lecturers to strengthening publication literacy among teachers as part of improving professionalism.